Career advancement comparative perspective study of university lecturer - Maya Kurniawati; Choirul Saleh; M.R. Khairul Muluk (Jurnal Konseling dan Pendidikan, 2021)
Globalization and international standard universities trend drive the higher education system to become more dynamic and innovative. The lecturer is a profession that drives and encourages university competitiveness. Therefore, better career advancement and development are vital in encouraging higher education competitiveness. The United States of America (USA) is currently a world-class university orientation, followed by Australia. Hence, other countries, especially developing countries, should know the USA and Australia higher education system, especially in the lecturers’ career advancement and development. This study is necessary to answer research questions about comparing academic career advancement systems in the USA and Australia. This study will give other countries new insight into academic career advancement. The researchers apply the findings from a systematic review. This study focuses on six aspects discussed: regulations, educational qualifications, lecturer obligation status in the higher education, career ladder, career advancement stages, and the lecturers' duties also responsibilities in lecturer career advancement in the USA and Australia. This study examines the gap between lecturers' career advancement systems in the USA and Australia comprehensively. The researchers observe by analyzing the strengths and weaknesses of the lecturer career advancement system in the USA and Australia. Also, the researchers compare the results using comparative public administration theory.